PENGARUH SELF-EFFICACY PADA PENERIMAAN E-RAPOR SMP - Gunawan Gunawan; Muhammad Rizki Zulkarnain (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2021)
This study aims to analyze the e-Rapor acceptance of junior high school using Extended Technology Acceptance Model (TAM) by including Self-Efficacy factor in the model. Data collection instrument in the form of questionnaire consisting of 19 points of statement and using 5 Point-Likert scale. The respondents were 60 e-Rapor users at public junior high school in Banjarmasin. The research data was analyzed using Partial Least Square-Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS 3.3.2 software. Based on the results of the study, it is known that Self-Efficacy has a directly positive and significant influence on the Behavioral Intention to use e-Rapor.